Relationship between estimated desaturase enzyme activity and metabolic syndrome in a longitudinal study - Domínguez-López, Inés; Arancibia-Riveros, Camila; Tresserra-Rimbau, Anna; Castro-Barquero, Sara; Casas, Rosa; Vázquez-Ruiz, Zenaida; Ros, Emilio; Fitó, Montserrat; Estruch, Ramon; López-Sabater, M. Carmen; Lamuela-Raventós, Rosa M. (Frontiers in Nutrition, 2022)
Desaturase enzyme activities (DEA) are associated with several metabolic diseases. The aim of the present study was to assess the relationship between estimated plasma DEA and the metabolic syndrome (MetS), as well as their relationship with individual components of the MetS. We conducted a longitudinal study of 148 participants recruited at random from the PREDIMED trial (Hospital Clinic site). At baseline and after 1 year of follow-up, DEA were estimated from product/precursor ratios of individual plasma fatty acids. Logistic regressions were used to assess the relationship of estimated DEA MetS, adjusted for potential cofounders. Estimated Δ5 desaturase (D5D) activity was associated with lower risk of MetS, whereas stearoyl-CoA (SCD) -16 and SCD-18 were negatively associated with MetS status. SCD-16, SCD-18, and Δ6 desaturase (D6D) were positively associated with triglycerides, SCD-18 was inversely associated with HDL-cholesterol. Estimated D6D activity was found to be associated with increases in diastolic blood pressure. In contrast, D5D was negatively associated with triglycerides, diastolic blood pressure and waist circumference. The present longitudinal study suggests that estimated SCD-16, SCD-18, and D6D have a negative impact in MetS and its components, whereas D5D may have beneficial effects for metabolic health.